Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis

Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques